2019
DOI: 10.1097/md.0000000000017554
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rupture of solid pseudopapillary tumor of pancreas

Abstract: Introduction: Solid pseudopapillary tumors (SPT) account for 1% to 3% of all pancreatic tumors. They have low malignant potential with a favorable prognosis, and predominantly occur in young women. The pathogenesis and clinical behavior of SPT are still uncertain. In addition, most ruptures of SPT were associated with blunt abdominal trauma, while spontaneous ruptures seemed to be quite rare. Up to now, there have been only 3 spontaneous ruptured SPT cases reported worldwide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…In the literature, rupture of the SPN is associated with abdominal trauma or may be spontaneous, which is rare. To date, there have been only 3 cases of SPN with spontaneous rupture reported worldwide [23]. In our series, we had two young patients with blunt abdominal trauma who underwent imaging exams that suspected hematoma (1) and pseudocyst (1).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, rupture of the SPN is associated with abdominal trauma or may be spontaneous, which is rare. To date, there have been only 3 cases of SPN with spontaneous rupture reported worldwide [23]. In our series, we had two young patients with blunt abdominal trauma who underwent imaging exams that suspected hematoma (1) and pseudocyst (1).…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous rupture of pancreatic tumors is an unusual course. There are some reports of spontaneous rupture of primary pancreatic tumors, such as cystic pancreatic tumors, SPN, and intraductal papillary mucinous neoplasms [1][2][3][4][5][6]. Some pregnancy-related cystic pancreatic tumors have the potential to grow and rupture during pregnancy [1,11].…”
Section: Discussionmentioning
confidence: 99%
“…The spontaneous rupture of a pancreatic tumor is an uncommon occurrence, although ruptured cystic pancreatic tumors, solid pseudopapillary neoplasms (SPN), and intraductal papillary mucinous neoplasms have been reported [1][2][3][4][5][6]. Metastatic tumors to the pancreas account for approximately 2% of all pancreatic tumors [7], and spontaneous rupture of metastatic pancreatic tumors is extremely rare [8].…”
Section: Introductionmentioning
confidence: 99%
“…One of the rare presentations of SPNs is tumor rupture that is commonly seen after blunt abdominal trauma, which has been reported to represent 8% of the cases (17,22). Interestingly, Xu et al reported a spontaneous rupture of SPN in a 22 years old female who presented to the Emergency Department (ED) complaining of abdominal pain associated with leukocytosis and hemoglobin drop secondary to spontaneous SPN rupture and bleeding (22).…”
Section: A B Cmentioning
confidence: 99%
“…One of the rare presentations of SPNs is tumor rupture that is commonly seen after blunt abdominal trauma, which has been reported to represent 8% of the cases (17,22). Interestingly, Xu et al reported a spontaneous rupture of SPN in a 22 years old female who presented to the Emergency Department (ED) complaining of abdominal pain associated with leukocytosis and hemoglobin drop secondary to spontaneous SPN rupture and bleeding (22). The suggested theory of spontaneous rupture is that the cystic part of the SPN undergoes internal degeneration with a subsequent hemorrhage; consequently, if the bleeding was significant enough, it can lead to increased intramural pressure causing the spontaneous rupture (17,22).…”
Section: A B Cmentioning
confidence: 99%